Preconception care of women with diabetes: a review of current guideline recommendations - Mazza Danielle; Mahmud Maimunah (BMC, 2010)
Abstract Background The prevalence of type 2 diabetes mellitus (T2DM) continues to rise worldwide. More women from developing countries who are in the reproductive age group have diabetes resulting in more pregnancies complicated by T2DM, and placing both mother and foetus at higher risk. Management of these risks is best achieved through comprehensive preconception care and glycaemic control, both prior to, and during pregnancy. The aim of this review was to compare the quality and content of current guidelines concerned with the preconception care of women with diabetes and to develop a summary of recommendations to assist in the management of diabetic women contemplating pregnancy. Methods Relevant clinical guidelines were identified through a search of several databases (MEDLINE, SCOPUS and The Cochrane Library) and relevant websites. Five guidelines were identified. Each guideline was assessed for quality using the AGREE instrument. Guideline recommendations were extracted, compared and contrasted. Results All guidelines were assessed as being of high quality and strongly recommended for use in practice. All were consistent in counselling about the risk of congenital malformation related to uncontrolled blood sugar preconceptionally, ensuring adequate contraception until glycaemic control is achieved, use of HBA1C to monitor metabolic control, when to commence insulin and switching from ACE inhibitors to other antihypertensives. Major differences were in the targets recommended for optimal metabolic control and opinion regarding the usage of metformin as an adjunct or alternative treatment before or during pregnancy. Conclusions International guidelines for the care of women with diabetes who are contemplating pregnancy are consistent in their recommendations; however some are more comprehensive than others. Having established current standards for the preconception care of diabetic women, there is now a need to focus on guideline implementation through an examination of the barriers and enablers to successful implementation, and the applicability of the recommendations in the local setting.